Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/cancers13236127
|View full text |Cite
|
Sign up to set email alerts
|

A Network-Based Approach to Glioma Surgery: Insights from Functional Neurosurgery

Abstract: The evaluation and manipulation of structural and functional networks, which has been integral to advancing functional neurosurgery, is beginning to transcend classical subspecialty boundaries. Notably, its application in neuro-oncologic surgery has stimulated an exciting paradigm shift from the traditional localizationist approach, which is lacking in nuance and optimization. This manuscript reviews the existing literature and explores how structural and functional connectivity analyses have been leveraged to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“… 36–38 Nevertheless, initial studies in glioma patients suggested that evaluating brain networks may help further elucidate the cognitive decline of various domains. 13–15 , 39 , 40 In the present study, we hypothesized that decreased structural connectivity in whole-brain networks is associated with cognitive deterioration in glioma patients. Therefore, we applied an innovative tractography algorithm 4 , 23 in combination with a network-based parcellation that allowed the construction of a whole-brain connectome of the structurally altered brain of pretreated glioma patients in conjunction with a well-developed method for predicting traits and symptoms from connectivity data.…”
Section: Discussionmentioning
confidence: 93%
“… 36–38 Nevertheless, initial studies in glioma patients suggested that evaluating brain networks may help further elucidate the cognitive decline of various domains. 13–15 , 39 , 40 In the present study, we hypothesized that decreased structural connectivity in whole-brain networks is associated with cognitive deterioration in glioma patients. Therefore, we applied an innovative tractography algorithm 4 , 23 in combination with a network-based parcellation that allowed the construction of a whole-brain connectome of the structurally altered brain of pretreated glioma patients in conjunction with a well-developed method for predicting traits and symptoms from connectivity data.…”
Section: Discussionmentioning
confidence: 93%
“…In traditional glioma surgery, lesion localization primarily depends upon the neurosurgeon’s understanding and experience with imaging data. After craniotomy, the brain sulcus depth, gyrus shape, color and blood vessel flow are observed and estimated ( 1 , 47 , 48 ). The above indications cannot be used to accurately evaluate the entire lesion contour.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth patterns could be further assessed with large-scale data using normative structural connectomics. Two recently published reviews also suggest the application of brain connectomics for glioma surgery [50,51]. Similarly, understanding tumor behaviors and associated symptoms might require a whole-brain approach [52].…”
Section: Neuro-oncology Applicationsmentioning
confidence: 99%